Integrated pest management - what future in the Third World? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
The advantages of Integrated Pest Management (IPM) for farmers in developing countries have been clear for many years. It cuts production costs by reducing reliance on expensive agrochemicals, reduces hazards to both humans and the environment and,...